LINGKUNGAN HIDUP dan LIBERALISASI PERDAGANGAN GLOBAL mendamaikan yang ‘tidak’ dapat damai (Suatu Analisis Politik Internasional) - Ruslin, Ismah Tita (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2014)
This writing describes a great rivalry between environmental and economical interests. When experts on environment are worried that free trade may create harm on natural resources as it has been allegedly blamed to bring about environmental disaster, the supporters of free trade are concerned that policies on environment may lead to huge breakdown in trading activities. Taken that to match the two might be difficult, if not impossible, this writing is trying to harmonize them. Through communicative action, the writer applies possibly compromised gaps, in order that our merely one world will continuously provide the needs of human beings for nowadays and for the future.